Membangun Pendidikan Karakter di Era Digital - Kasful Anwar Us (INNOVATIO: Journal for Religious Innovation Studies, 2018)
Modern technology has enabled the creation, cross-country, free communication across rural areas and densely populated areas in cities. Through connection devices with internet capabilities, social media such as facebook, twitter, Instagram and whatsapp also reach all corners, but on the other hand interfere the focus of learning millennial generation. The new media even offers new characters through shows good and beautiful. This paper aims to unravel the opportunities and challenges of character education in the current digital era. Character education have to be carried out simultaneously. In the context of Indonesia based on noble values ​​contained in Islamic teachings, Pancasila, Basic Law of 1945, Sumpah Pemuda spirit, the views and thoughts of the nation’s leaders, and values ​​of local wisdom. The process must be developed in order character education run simultaneously is through participatory, involving multi-parties and humanists based on Islamic and Indonesian values.